Aspects of Computational Thinking observed in problem-solving in 6th grade Mathematics textbooks of Middle School - Coelho, Janaína Aparecida Ponté; Barrére, Eduardo (Educação Matemática Debate, 2025)
The research observed how aspects of Computational Thinking manifest themselves in problem-solving in sixth-grade Mathematics textbooks, considering that these materials are among the most used by Basic Education teachers. For this analysis, the concept of Computational Thinking in Mathematics Education was adopted. Thus, characteristics aligned with Computational Thinking were identified both in activities similar to the questions covered in the textbooks and in the activities solved by the students, which highlights the possibility of designing teaching methodologies that integrate Computational Thinking into the activities presented in these materials.